Determining the frequency of regular dental visits and its association with the current oral status of children - Munawwar, Soha; Tariq, Hira; Khatoon, Naushaba; Ahmer, Zaeema (Journal of the Pakistan Medical Association, 2026)
Objectives: To determine the frequency of regular dental visits, the oral health status of school children, and to assess the awareness of parents regarding these visits. Method: The cross-sectional study was conducted from January to October 2023 at a private school in Karachi after approval form the ethics review board of Jinnah Sindh Medical University, Karachi, and comprised children aged 6-12 years from grades 1-6. Data was collected from the parents of the enrolled children using a pilot-tested structured questionnaire. This was followed by oral examination of the children. Data was analysed using SPSS 20. Results: Of the 345 subjects with mean age 9.5±1.49 years, 197(57.1%) were boys and 148(42.9%) were girls. Among the parents, 146(42.3%) had at least three children. Overall, 145(42%) children had never visited a dental clinic. Among the 200(58%) who had visited a dentist, Regular visits were reported by 21(10.5%). Among the parents, 205(59.4%) were aware of the importance of regular dental visits. Caries were found in 158(45.8%) children, while the mean plaque score was 0.74±0.93. The incidence of caries and presence of plaque were significantly lower among children who had been visiting dentists regularly (p<0.05). A significant association was seen between regular dental visits and children with only one sibling (p=0.004). Conclusion: The frequency of regular dental visits was found to be low. The high prevalence of caries emphasised the importance of regular dental visits. Key Words: Dental health services, Dental care, Dental care for children.